Kesusastraan Kontemporer Cina: Kontemporeritas dan Kebijakan Pemerintah - Wuryandari, Nurni W. (Wacana, Journal of the Humanities of Indonesia, 2006)
What is meant by contemporary literature? The first thing that comes up in mind is that the terminology of contemporary literature points out to "literature that is new" or "literature that is very recent", and constitutes a new trend lastly in touch with public. With this, contemporarity might possibly be seen or measured on the basis of time frame. In China, contemporary literature is not measured merely by the most recent time and the changing literary trend in a certain period of time, it is apparently not free from the political influence of the goverment in power. Political guidance issued by the goverment in a certain period, will define the change in the literary trend in China. Uniquely, the literary trend in a certain period not merely brings out certain themes, but also followed by a great deal of literary works representing the emerging literary trend. In China, by reading a literary work, one will easily be able to detect when that kind of literary works approximately emerged, and who were the authors producing that works.